Pengembangan E-Modul Pembelajaran Rias Wajah Cikatri Pada Kulit Pigmentasi Berbasis Canva - Luthfiyana, Luthfiyana; Supiani, Titin; Hidayah, Nurul (Innovative: Journal Of Social Science Research, 2025)
This research is motivated by the insufficient diversity of engaging digital learning resources and the absence of autonomous learning materials. This project aims to create an e-module utilising Canva as a learning medium for Cikatri Makeup on pigmented skin, specifically for the Beauty Administration program at SMK Laboratorium Jakarta. The employed research methodology is research and development utilising the 4D development paradigm (define, design, develop, disseminate). Product validation is conducted by feasibility testing by material and media specialists. The validation findings for material I were 93.3%, while those for material II were 98.6%. The outcomes of media expert validation in stage I were 92.3%, while stage II yielded 94.2%. Subsequently, researchers executed a practicality trial for students at the Jakarta Vocational Beauty Laboratory. The practicality trial was executed in two phases: a one-on-one trial stage with three students, yielding a result of 94.3%, and a small group trial done with nine students, resulting in 95%. The findings of this study demonstrate that the Cikatri Makeup E-Module for Pigmented Skin is legitimate, viable, and practical as a learning medium.